Towards more feasible sovereign debt restructurings in the euro area - Frederik Eidam; Friedrich Heinemann (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Over the last year, exchanges that were initiated by the ZEW's SEEK-conference on `regulating sovereign debt restructuring in the eurozone' resulted in vivid discussions on more feasible sovereign debt restructurings in the euro area. This policy report, edited by Frederik Eidam and Friedrich Heinemann, summarizes these discussions by collecting several contributions on different aspects of the topic. Founded in different perspectives, contributors sometimes provide different conclusions, or highlight different choice options and their underlying trade-offs. However, common to all authors is the aim to increase the resilience of the European Monetary Union and to contribute on the debate on the European reform agenda.
Keywords: 330